Lake Chad Regional Economic Memorandum : Technical Paper 5. Conflict and Climate Change in the Lake Chad Region - Fisker, Peter (World Bank, Washington, DC, 2021)
Peace and security are basic conditions for economic and social development. Conflict, on the other hand, can reverse years of economic growth and induce long-term harm on almost all aspects of development. For the past decade, the Lake Chad region has been the setting of conflicts between government forces and armed groups, most notably the Boko Haram. Although the intensity of fighting has petered off in recent years, the conflict has spread from Northern Nigeria and now affects all four countries of the region. Due to the paramount importance of avoiding armed conflict, a large economic literature exists that seeks to find explanations for the onset and prevalence of conflict in developing countries. Blattman and Miguel [2010] list some of the most common theories of conflict including competition for resources, economic grievances, and the possibility of looting. This paper attempts to shed light on the geographical distribution of conflict and its climatic determinants in the Lake Chad region following a sub-national approach where readily available spatial data is employed at two different units of aggregation: Firstly, 90 second level administrative areas, and secondly, around 5,318 grid cells covering the same region. Exposure to conflict is here defined as the intensity (for districts) or incidence (for cells) of conflict in a given unit each year. Parts of the population may not be directly exposed by this definition, but since the units of analysis are relatively small, most will be affected in some ways, for instance by safety concerns when visiting the nearest towns to trade or by the general economic consequences.